2016
DOI: 10.1002/app.43343
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of trypsin onto thermo‐sensitive poly(N‐isopropylacrylamide‐co‐acrylic acid) microspheres with high activity and stability

Abstract: Poly(N-isopropylacrylamide-co-acrylic acid) (P(NIPAM-co-AA)) microspheres with a high copolymerized AA content were fabricated using rapid membrane emulsification technique. The uniform size, good hydrophilicity, and thermo sensitivity of the microspheres were favorable for trypsin immobilization. Trypsin molecules were immobilized onto the microspheres surfaces by covalent attachment. The effects of various parameters such as immobilization pH value, enzyme concentration, concentration of buffer solution, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Below their LCST, the same polymer is translucent in aqueous media and hydrophilic (i.e., hydrated/swollen state). At the LCSTs or phase separation temperatures, the cross-linked polymer chains undergo a volume phase transition (VPT)—The polymers expand below the LCST, and collapse above the LCST [3,5,9,10]. The phase transitions of these polymers are usually reversible upon the heating and cooling cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Below their LCST, the same polymer is translucent in aqueous media and hydrophilic (i.e., hydrated/swollen state). At the LCSTs or phase separation temperatures, the cross-linked polymer chains undergo a volume phase transition (VPT)—The polymers expand below the LCST, and collapse above the LCST [3,5,9,10]. The phase transitions of these polymers are usually reversible upon the heating and cooling cycle.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39] A small amount of acrylic acid (AA) was added during polymerization to functionalize the SiO 2 @PNIPAM microspheres with carboxyl groups, so that urease can be further immobilized on the surface through EDC/NHS method. [31] As a temperature-responsive polymer, PNIPAM can shrink when the temperature is higher than its LCST and swell reversibly at lower temperature. Herein, the thermal sensitivity of PNIPAM is used to protect the activity of urease, as it is anticipated that the inactivation of enzyme due to the deformation of the protein chains can be partially inhibited by the shrinkage of PNIPAM at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The immobilized trypsin maintained 91% of its initial activity after storage at 45 °C for 60 min comparing with only 60% for the free trypsin. [31] Liu et al found that the PNIPAM chains constructed a unique microenvironment for lipase to improve its thermal stability. [32] The entrapped trypsin exhibited more than 70% of its initial activity after treatment at 90 °C for 2 h, while the residual activity of free trypsin was only 3%.…”
Section: Introductionmentioning
confidence: 99%
“…The thermoresponsive polymer known as poly-N-isopropylacrylamide (PNIPAm) is among the most widely researched stimuli-responsive polymers. The applications of PNIPAm are mainly related to the areas of drug delivery [3][4][5] and the immobilization as well as adsorption of enzymes and proteins [6]. This is partially due to inherent physical properties, which are modulated by the reversible phase separation behavior.…”
Section: Introductionmentioning
confidence: 99%